Immunohistochemistry is highly sensitive and specific for the detection of V600E BRAF mutation in melanoma - Long, Georgina; Wilmott, James S.; Capper, David; Preusser, Matthias; Zhang, Yuxiao E.; Thompson, John F.; Kefford, Richard F.; Deimling, Andreas von; Scolyer, Richard A. (The American journal of surgical pathology, 2013)
This study investigated the sensitivity and specificity of immunohistochemical (IHC) analysis using an anti-BRAF antibody to detect the presence of the BRAF V600E mutation in patients with metastatic melanoma. A total of 100 patients with American Joint Committee on Cancer stage IIIC unresectable or stage IV melanoma and who underwent tumor DNA BRAF mutation testing were selected. Paraffin-embedded, formalin-fixed melanoma biopsies were analyzed for the BRAF mutation status by independent, blinded observers using both conventional DNA molecular techniques and IHC with the novel BRAF V600E mutant-specific antibody, VE1. The antibody had a sensitivity of 97% (37/38) and a specificity of 98% (58/59) for detecting the presence of a BRAF V600E mutation. Of the BRAF-mutated cases, none of the non-V600E cases (including V600K) stained positive with the antibody (0/11). There were 5 cases with discordant BRAF mutation results. Additional molecular analysis confirmed the immunohistochemically obtained BRAF result in 3 cases, suggesting that the initial molecular testing results were incorrect. Two of these patients would not have received a BRAF inhibitor on the basis of the initial false-negative mutation testing result. Two cases remained discordant. The reported IHC method is an accurate, rapid, and cost-effective method for detecting V600E BRAF mutations in melanoma patients. Clinical use of the V600E BRAF antibody should be a valuable supplement to conventional mutation testing and allow V600E mutant metastatic melanoma patients to be triaged rapidly into appropriate treatment pathways.
Gesehen am 20.05.2021